Aspects of the population ecology, habitat use and behaviour of the endangered Knysna seahorse (Hippocampus capensis Boulenger, 1900) in a residential marina estate, Knysna, South Africa: implications for conservation - Claassens, Louw (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2018)
The Knysna seahorse Hippocampus capensis is South Africa's only endemic seahorse species, and is found in only three adjacent estuaries along the southern coast. The conservation of this endangered species is important on a national and international level. This study presents the first research on this species within the Knysna estuary since 2001 and specifically focuses on aspects of its ecology within a residential marina estate (Thesen Islands Marina). The physico-chemical and habitat features of the marina were described and the population ecology, habitat use, and behaviour of the Knysna seahorse were investigated. Physico-chemical conditions within the western section of the marina, characterised by high water current velocities, were similar to that of the adjacent estuary. The eastern section of the marina was characterised by lower water current velocities and higher turbidity. Four major habitat types were identified within the marina canals: (I) artificial Reno mattress (wire baskets filled with rocks); (II) Codium tenue beds; (III) mixed vegetation on sediment; and (IV) barren canal floor. Seahorse densities within the marina were significantly higher compared to densities found historically within the estuary. Highest seahorse densities were specifically found within the artificial Reno mattress structures and within the western section of the marina. Seahorse density varied spatially and temporally and the type of habitat was an important predictor for seahorse occurrence. An experimental investigation found that H. capensis chooses artificial Reno mattress habitat over Zostera capensis when given a choice. GoPro cameras were used successfully to investigate daytime seahorse behaviour within the Reno mattress habitat. Seahorses were more active during the morning, spent most of their time (> 80 %) feeding, and morning courting behaviour for this species were confirmed. However, during the summer holiday period (mid-December to mid-January) few seahorses were observed on camera, which suggests that the increase in motor boat activity and the related increase in noise had a negative effect on H. capensis feeding and courting behaviour. The marina development, and in particular the Reno mattresses, created a new habitat for this endangered species within the Knysna estuary. In addition to the protection and restoration of natural habitats in which H. capensis is found, the conservation potential of artificial structures such as Reno mattresses should be realised.
Keywords: Endangered species -- South Africa -- Knysna; Sea horses -- Behavior -- South Africa -- Knysna; Sea horses -- Habitat -- South Africa -- Knysna; Sea horses -- Ecology -- South Africa -- Knysna